(ii) (2a + 3b)2 – 2(2a + 3b)(2a – 3b) + (2a + 3b)2 gla 1)2 + 2a + 1) (2) 15( 1212​

Question

(ii) (2a + 3b)2 – 2(2a + 3b)(2a – 3b) + (2a + 3b)2

gla
1)2 + 2a + 1) (2)
15(
1212​

in progress 0
Maya 1 month 2021-08-16T20:21:05+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-16T20:22:23+00:00

    Answer:

    The answer will be 24ab + 36b^2

    Please mark my answer as the brainliest

    0
    2021-08-16T20:22:57+00:00

    Answer:

    =(2a+3b)²-2(2a+3b)(2a-3b)+(2a-3b)²

    ={2a+3b-(2a-3b)}²

    =(2a+3b-2a+3b)²

    =(6b)²

    =36b²

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )